2011
DOI: 10.1007/s11547-011-0730-5
|View full text |Cite|
|
Sign up to set email alerts
|

MR-diffusion imaging in assessing chronic liver diseases: does a clinical role exist?

Abstract: Our results indicate that stratifying patients with chronic liver disease for clinical purposes cannot be done with DWI. However, there is a tendency among groups for reduced perfusion-related parameters as chronic liver disease progresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…It must be underlined that these differences did not change the diagnostic power of PF and ADC: in fact, both are lower in patients affected by liver cirrhosis regardless of CA administration, as reported in Table . In particular, the reduction of PF with the progression of diffuse liver disease has been observed in other studies and can be explained considering that the capillary network diminishes in the cirrhotic liver. Moreover, it should be underlined that CA administration did not determine a bias in all the parameters, and this can be observed as numeric values (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…It must be underlined that these differences did not change the diagnostic power of PF and ADC: in fact, both are lower in patients affected by liver cirrhosis regardless of CA administration, as reported in Table . In particular, the reduction of PF with the progression of diffuse liver disease has been observed in other studies and can be explained considering that the capillary network diminishes in the cirrhotic liver. Moreover, it should be underlined that CA administration did not determine a bias in all the parameters, and this can be observed as numeric values (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Diffusion-weighted imaging showed a more limited capability to distinguish between different grades of liver fibrosis (9,10,12). Contrast-enhanced MR imaging in retrospective studies also showed relatively high accuracies in the detection of advanced liver fibrosis, depending on the sequence and scoring system (14,34).…”
Section: Discussionmentioning
confidence: 99%
“…Technical advances in magnetic resonance (MR) imaging have enabled attempts to assess CLD by using diffusion-weighted imaging (9,10), perfusion-weighted MR imaging (11), MR elastography (12), MR spectroscopy (13), contrast material-enhanced MR imaging (14), T2* mapping (15), and susceptibility-weighted (SW) imaging (16,17).…”
Section: Patientsmentioning
confidence: 99%
“…Several studies, in the past fifteen years, have investigated its contribution in the assessment of diffuse and focal hepatic disease [ 7 , 20 , 21 ]. Important researches have evaluated DWI capability in the quantification of hepatic fibrosis in chronic liver disease [ 7 , 22 , 23 ], in characterization and detection of focal liver lesions [ 24 26 ], and in monitoring response to treatment in oncological patients [ 27 , 28 ].…”
Section: Assessment Of Hepatic Fibrosis Using Diffusion-weighted Mmentioning
confidence: 99%